A comparative study of competitive ability between two cactophilic species in their natural hosts - Werenkraut, Victoria (2008)
Competition is a major aspect of the ecology of insect communities exploiting ephemeral and fragmented resources.We analysed the effect of intraspecific (single species culture) and interspecific (mixed species culture) competition on larval viability, developmental time and wing length in the cactophilic Drosophila buzzatii and Drosophila koepferae (Diptera: Drosophilidae) reared in cultured media prepared with fermenting tissues of three common natural cactus hosts in nature at different densities. Our results show that all traits measured were affected by both intra- and interspecifc competition, although the effect of competition depended on the Drosophila species and the rearing cactus. In fact, flies tended to have a lower viability, shorter wing size and longer developmental time as a function of increasing density in single species culture in both D. buzzatii and D. koepferae (intraespecific competition). Besides, the performance of both species was seriously affected (shorter body size, slower developmental times, lower viability) by the presence of heterospecific competitors except in the case of D. koepferae reared in its primary host plant, Trichocereus terschekii. We also show that D. koepferae successfully utilized Opuntia quimilo, which is absent in most parts of its distribution range.We discuss the roles of intra- andinterspecific competition as determinants of the relative abundance of these two species in the arid zones of Southern South America.